1999
DOI: 10.1143/jjap.38.l301
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Ultrathin Epitaxial 3C-SiC Films on Si(100) by Pulsed Supersonic Free Jets of CH3SiH3

Abstract: We propose a novel resonant detector of terahertz radiation based on a heterostructure with an ungated two-dimensional electron channel, with a lateral Schottky junction at one of the channel edges, substantiate its operation, and evaluate the device characteristics. We demonstrate that the detector responsivity can exhibit sharp resonant maxima at the frequencies pertaining to the plasma oscillations. As shown, the peak values of the responsivity of the detector proposed can exceed the responsivity of the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 7 publications
5
32
1
Order By: Relevance
“…This shows that the film deposition stops within 1 minute. This coincides with those obtained by Ikoma et al (Ikoma., 1999) and Boo et al (Boo et al, 1999) using monomethylsilane gas. Fig.…”
Section: Chemical Reaction In Monomethylsilane and Hydrogen Chloride supporting
confidence: 93%
“…This shows that the film deposition stops within 1 minute. This coincides with those obtained by Ikoma et al (Ikoma., 1999) and Boo et al (Boo et al, 1999) using monomethylsilane gas. Fig.…”
Section: Chemical Reaction In Monomethylsilane and Hydrogen Chloride supporting
confidence: 93%
“…(1)- (8), are expected to affect the film composition. Si 2 H x is very easily decomposed to produce silicon clusters in the gas phase or on the substrate surface, in Eq.…”
Section: Article In Pressmentioning
confidence: 99%
“…Here, methylsilanes, such as monomethylsilane and dimethylsilane, are expected to allow lower temperature silicon carbide film formation than the ordinary technique using silane and hydrocarbon gases, such as propane [2,3], because methylsilanes have a covalent bond between the silicon and carbon in its molecular structure. Thus, many researchers have studied silicon carbide film formation technology using monomethylsilane gas [4][5][6][7][8][9][10][11][12], as well as dimethylsilane [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent various studies [5][6][7][8][9][10][11][12][13][14][15][16][17] also succeeded in producing SiC films on Si using various deposition methods with methylsilane. In those studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17], methylsilane was selected as a gas source because the methylsilane molecule has a Si-C bond and its stoichiometric composition (atomic concentration ratio of Si to C) is the same as that of SiC. On the other hand, Xu et al reported that the dissociative adsorption of methylsilane onto the Si surface broke the Si-C bond [18].…”
Section: Introductionmentioning
confidence: 99%